Pengaruh Aplikasi PGPR dan Jenis Pestisida terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) - Yunitha Maria Naikofi; Aloysius Rusae (Fakultas Pertanian, Universitas Timor, 2017)
The aim of this research is to know PGPR application frequency and the type of pesticide that's right for growth and yield of lettuce. The experimental design used was a Factorial Randomized Block Design 3 x 3 with three replications. The first factor is PGPR application consisting of three levels ie, without PGPR, watering once a week, watering every two weeks. The second factor is pesticide type with three levels ie without pesticide, betel leaf extract pesticide, and biological pesticide. The study was conducted from February to March 2017 in the experimental garden of the Faculty of Agriculture, Timor University. The results showed that there was no interaction effect between PGPR application and pesticide type on growth and lettuce yield. PGPR application only has a significant effect on root dry weight, whereas pesticide type only influences to dry weight of yields. PGPR application once two-week yields the most heavily plated lettuce (253.71 g), while the type of pesticide that produces the most weight lettuce is biological pesticide (198.38 g).